Current Approaches to the Use of Innovative Technologies in the Teaching of Foreign Languages in Higher Educational Institutions - Oksana Voitik (Pedagogical Discourse, 2012)
The article is devoted to the modern approaches to the use of innovative technologies in the teaching of foreign languages ​​in higher educational institutions. Additional means for better learning of new vocabulary, grammar, and educational material, the educational process through the use of educational technology